Impact of Employees’ Turnover on the Performance of Five Star Hotels of Kathmandu - Shrestha, Bijaya; Thapa, Roshan (Kathford Journal of Engineering and Management, 2023)
This study examined the Impact of Employee Turnover on the Performance of Five five-star hotels. Data was collected from the 120 hotel employees from six hotels in Kathmandu using the questionnaire. The employees were randomly sampled. Jamovi was used to run the analysis. While collecting the data among the respondents, 91 (75.8%) were Male, and 29 (24.2%) were female. Likewise, 64 (53.3%) were staff, 36 (30.0%) were supervisors, and 20 (16.7%) were heads of departments. Out of 120 respondents, 51 respondents (42.5%) had worked in the respective hotel for